A Survey Examining Photopatch Test and Phototest Methodologies of Contact Dermatologists in the United States: Platform for Developing A Consensus. Issue 4 (July 2017) - Asemota, Eseosa; Crawford, Glen; Kovarik, Carrie; Brod, Bruce A.
Abstract : Background: There is currently no standardized protocol for photopatch testing and phototesting in the United States. Certain testing paramaters (such as chemicals tested, time between test application and irradiation, and time of final interpretation) vary from provider to provider. These variations may impact comparability and consistency of test results. Objective: The goal of our survey-based study was to outline the photopatch test and phototest protocols used by US contact dermatologists. The information obtained will aid in the development of a national consensus on testing methodologies. Methods: Based on a literature search conducted on differences in testing methodologies, we constructed a questionnaire. The survey was distributed at the American Contact Dermatitis Society annual meeting and via the American Contact Dermatitis Society Web site. Standard descriptive analysis was performed on data obtained. Results: Of the 800 dermatologists contacted, 117 agreed to participate in the survey. Among these respondents, 64 (54.8%) conduct photopatch testing. Results of the survey are presented, and they confirm that a variety of techniques and testing materials are used. Conclusions: It would be beneficial to enlist a panel of expert contact dermatologists to create by formal consensus, using these research findings, a standard photopatch test protocol for use in this country.